Changes in serum magnesium concentration after use of a proton pump inhibitor in patients undergoing percutaneous coronary intervention - Sang-Ho Park; Sun-hyo Lee; Ji-Sung Lee; Won-Yong Shin; Hyo-Wook Gil; Jong-Oh Yang; Eun-Young Lee; Sae-Yong Hong (The Korean Society of Nephrology, 2015)
Background: Although cross-sectional studies have suggested a relationship between proton pump inhibitor (PPI) use and hypomagnesemia, no large-scale cohort study has been conducted to date. Here, we examined the changes in serum magnesium levels in response to PPI use. We hypothesized that PPI use might change the serum magnesium concentration. Methods: Of the 2,892 patients hospitalized for percutaneous coronary intervention between January 2007 and May 2012, 1,076 patients with normal baseline (1.6-2.5 mg/dL) and follow-up serum magnesium concentrations were enrolled. These patients were divided into two groups: the PPI group and the control group. Results: The mean follow-up period was 9.51±2.94 months. The incidence of hypomagnesemia (<1.6 mg/dL) was 0.4% (3/834) in the PPI group and 0.4% (1/242) in the control group (P =0.904). The change in magnesium levels did not differ between the two groups, and this result was maintained in the analysis of covariance after adjusting for confounding factors (P = 0.381). Moreover, magnesium levels did not significantly differ between the long-term (duration of use ≥12 months, n = 71) and short-term PPI groups (duration of use <12 months, n = 763), and the control group (n = 242; P = 0.620). The effect of PPI use on change in serum magnesium concentration was affected by the use of multiple diuretics (−0.01±0.25 mg/dL; P = 0.025), although a single diuretic use with PPI did not alter the change in magnesium level (0.12±0.27 mg/dL). Conclusion: Changes in magnesium levels might be subtle after PPI use in patients with normal baseline magnesium values.